AESTHETIC SATISFACTION AFTER THE SURGICAL TREATMENT OF FACIAL NMSC - 5 YEAR STUDY - Filip Ryszard Lachowski; Ewa Maria Lachowska; Magdalena Graczyk; Patrycja Jabłońska; Paulina Bernecka; Agnieszka Pruska; Natalia Domańska; Maria Krasnodębska; Julia Ogrodowczyk vel Ogrodowicz; Olga Łopatko; Karolina Wojdat-Krupa; Karol Sikora; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Background: Skin cancers are the most common malignant tumors, with nonmelanoma skin cancers (NMSCs) being the predominant group. In recent years, the diagnosis of NMSCs has increased. Today, patients are more sensitive to aesthetic outcomes, necessitating that surgeons also focus on the final appearance of the scar, especially in facial procedures. A satisfactory visual outcome significantly influences patients’ perception of comfort, quality of treatment, and overall quality of life. Methods: In our study, we surveyed patients who underwent surgery for facial skin cancer to assess their aesthetic satisfaction. We analyzed their responses based on six criteria: age, gender, number of tumor foci, lesion location, extent of excision, and tumor type. The questionnaire addressed satisfaction with the overall aesthetic effect, scar visibility, preserved facial symmetry, and willingness to recommend our clinic. Results and Conclusions: We collected responses from 698 patients. Among the questions, satisfaction was lowest for scar visibility. Gender did not show a statistically significant difference in satisfaction levels. Satisfaction with the aesthetic outcome decreased with age. Of the operated locations, the highest aesthetic satisfaction was noted for eye area excisions, and the lowest for the nose. The number of cancerous lesions did not affect aesthetic satisfaction. Both incomplete excisions and tumor recurrences lowered satisfaction, with recurrences having a more significant impact. Patients treated for basal cell carcinoma (BCC) reported greater satisfaction with the aesthetic outcome than those treated for squamous cell carcinoma (SCC).